Investigation into repetitive concussion in sport (RECOS): study protocol of a prospective, exploratory, observational cohort study - Kamal M Yakoub; David J Davies; Conor Bentley; Callum N Watson; Mario Forcione; Emma Toman; Douglas Hammond; Antonio Belli; Vijay Sawlani; Zhangjie Su; Jon Bishop; Lauren Cooper; et al. (BMJ Open)
Introduction Sport-related concussion management remains a diagnostic dilemma to clinicians in all strata of care, coaching staff and players alike. The lack of objective diagnostic and prognostic biomarkers and over-reliance on subjective clinical assessments carries a significant health risk of undiagnosed concussive episodes and early return to play before full recovery increasing the risk of sustaining additional concussion, and leading to long-term sequelae and/or unfavourable outcome.Objective To identify a set of parameters (neuroimaging with neurophysiological, biological and neuropsychological tests) that may support pitch-side and outpatient clinical decision-making in order to objectively diagnose concussion, determine the severity of injury, guide a safe return to play and identify the potential predictors of the long-term sequelae of concussion.Methods and analysis An exploratory, observational, prospective, cohort study recruiting between 2017 and 2020. The participants will have a baseline preseason screening (brain imaging, neuropsychological assessments, serum, urine and saliva sampling). If a screened player later suffers a concussion and/or multiple concussions then he/she will be assessed again with the same protocol within 72 hours, and their baseline data will be used as internal control as well as normative data. Inferential statistical analysis will be performed to determine correlations between biological, imaging techniques and neuropsychological assessments.Ethics and dissemination This study was approved by the East of England—Essex Research Ethics Committee on 22 September 2017—REC 17/EE/0275; IRAS 216703. The results of this study will be presented at national and international conferences and submitted for publication in peer reviewed journals.Trial registration number ISRCTN16974791; Pre-results.